With the adoption of the paris climate agreement, turkey's decarbonization roadmap and its position in the 26th conference of the parties (COP26) - FEYZİOĞLU, AHMET (My University, 2022)
Climate change is a substantial global threat with long-term effects on the countries’ sustainable development. The intersection of the sustainability and energy management is the climate change-based carbon management and decarbonization strategies. In line with Turkey's 2053 net-zero emission and green-development target; the purpose/scope of this study is to make an overall assessment of decarbonization strategies being developed on a national-scale with a focus on international trade, business, urban life/industry, finance and environment. After ratifying the Paris Agreement on October 2021, Turkey has also signed four commitments in COP26/Glasgow to tackle with the climate change. Now, Turkey has two significant actions before COP27/Egypt: Setting out/updating its Nationally Determined Contribution and preparation of long-term strategy with a vision of 2053 net-zero target. Turkey’s Climate Council-2022 will also determine the medium and long-term strategic targets/policies regarding the sectors. These will also provide technical framework for the Parliament’s Climate Law to be prepared.
Keywords: Decarbonization; Paris Agreement; Net-Zero; Energy Management; Sustainable Development